A Canadian framework for data reuse - Michel Girard (Centre for International Governance Innovation (CIGI), 2021)
Although Canada is making progress in protecting consumers against data misuse, it needs to turn its attention to enabling data reuse. The current practices and tools in place are not conducive for data sharing. This creates a significant hurdle for data scientists and statisticians as they cannot train algorithms without large data inputs. A national framework for data reuse is needed to manage risks associated with data sharing. It should include sector-based data strategies, the certification of new classes of data professionals across data value chains, common interoperability and governance standards, and a safe and secure data transmission infrastructure. As common data-sharing spaces are needed for data reuse to occur, there is an opportunity to experiment with different data-sharing models. A national data reuse framework is essential for Canada to assert its data sovereignty and become a digital society. This is why the federal government has a critical role to play.
Keywords: 330